2019
DOI: 10.3389/fnbeh.2019.00197
|View full text |Cite
|
Sign up to set email alerts
|

How Early Life Stress Impact Maternal Care: A Systematic Review of Rodent Studies

Abstract: Background: Maternal care refers to the behavior performed by the dam to nourish and protect her litter during its early development. Frequent and high-quality performance of such maternal behaviors is critical for the neurodevelopment of the pups. Maternal exposure to stress during early development can impair maternal care and amplify the deleterious effects of poor maternal caregiving and neglect. As such, a thorough understanding of the effects caused by several models of early life stress on ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 86 publications
(118 reference statements)
1
55
0
1
Order By: Relevance
“…However, during the MS paradigm, the threat tends to raise in response to the novel environment. On the other hand, in a recent review from our laboratory (Orso et al, 2019), we found that MS alone induces an increase in the levels of licking/grooming post-reunion. This counterbalance behavior (increase in maternal care) could attenuate the deprivation characteristics of the MS model, and possibly minimize the effects of the separation period (Davis et al, 2020;Wang et al, 2020).…”
Section: Discussionmentioning
confidence: 52%
“…However, during the MS paradigm, the threat tends to raise in response to the novel environment. On the other hand, in a recent review from our laboratory (Orso et al, 2019), we found that MS alone induces an increase in the levels of licking/grooming post-reunion. This counterbalance behavior (increase in maternal care) could attenuate the deprivation characteristics of the MS model, and possibly minimize the effects of the separation period (Davis et al, 2020;Wang et al, 2020).…”
Section: Discussionmentioning
confidence: 52%
“…Mice in the present study were exposed only to same-sex conspecifics, and many studies reporting sex differences in BNST-mediated behaviors attribute differences to mating or mating-related behaviors (Maejima, Ohishi, Yamaguchi, & Tsukahara, 2015;Wersinger, Baum, & Erskine, 1993), so it is possible that sex differences may have emerged here had we exposed mice to conspecifics of the opposite sex. Also of note, the majority of past mouse studies examining ELS effects have excluded females entirely or neglected to report comparisons between sexes (see Orso et al, 2019), so it is difficult to compare the reported frequency of BNST behavior-related sex differences in the literature to the present findings.…”
Section: Bnst-mediated Sex Effectsmentioning
confidence: 78%
“…To understand how ELS alters neurobiology in a way that promotes such aberrant behavior, many studies have used rodent models of maternal separation in which early postnatal pups are deprived of necessary maternal care by separating them from the dam for extended periods of time (for reviews see Nishi, Horii-Hayashi, & Sasagawa, 2014;Orso et al, 2019;Tractenberg et al, 2016). Rodent maternal separation during the early postnatal period has been shown to produce an array of adolescent and adulthood behavioral effects not limited to increased anxiety-like behavior (Caldji, Diorio, & Meaney, 2000;Daniels, Pietersen, Carstens, & Stein, 2004;Lee et al, 2007;Levine, 1967;Liu, Diorio, Day, Francis, & Meaney, 2000;Matthews, Hall, Wilkinson, & Robbins, 1996), hyper-responsiveness to stressors (Holmes et al, 2005;Meaney, 2001;Ogawa et al, 1994;Plotsky & Meaney, 1993), altered reward learning and cognition (Forster, Anderson, Scholl, Lukkes, & Watt, 2018;Liu et al, 2000;Matthews & Robbins, 2003;Portero-Tresserra et al, 2018;Pryce, Bettschen, Nanz-Bahr, & Feldon, 2003;Sasagawa et al, 2017), deviations in normal fear learning and memory (Callaghan, Graham, Li, & Richardson, 2013;Chocyk et al, 2014), and deficits in social behavior (Frank et al, 2019;Kompier, Keysers, Gazzola, Lucassen, & Krugers, 2019;Venerosi, Cirulli, Capone, & Alleva, 2003;Wang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Given the important role that maternal behaviors such as licking and grooming (LG) or arched-back nursing (ABN) play in the development of circuits that regulate defensive-exploratory behavior 23 it is important to consider the effects of MS on these behaviors in rats and mice. This issue was recently reviewed by Orso et al who found that MS induces higher levels of LG-ABN in rats compared to mice 46 . This increase in maternal behavior would expect to minimize and not to exacerbate the consequences of MS in rats.…”
Section: Discussionmentioning
confidence: 99%